Micropores within N, S co-doped mesoporous 3D graphene-aerogel enhance the supercapacitive performance. (13th April 2021) - Kumari, Shilpa; Verma, Ekta; Kumar, Rajinder; Upreti, Deepak; Prakash, Bhanu; Maruyama, Takahiro; Bagchi, Vivek
Abstract : Micropores within N, S co-doped mesoporous 3D graphene-aerogel enhances supercapacitive performance. Abstract : In energy storage applications, supercapacitors with high energy and high power density could be a game-changer for society, allowing us to power our lives. Currently, hetero-doped reduced graphene oxide (rGO) aerogels have attracted significant attention owing to their excellent performance in electrochemical and energy storage applications. Traditionally, similar electrode materials have been synthesized by a multiple-step process, such as carbonization and the activation of carbon precursors, which involves high energy consumption and tiresome procedures. Herein, a low-cost, simple, one-step method is developed to synthesize N, S co-doped 3D reduced graphene oxide aerogel-3 (NS-rGOA3) with highly enhanced micropores along with mesopores, high surface area and high conductivity. This innovative approach not only bypasses carbonization and activation processes but also provides a single-step method for the in situ preparation of nitrogen, sulphur co-doped 3-D rGO aerogels. NS-rGOA3 synthesized by the hydrothermal process has been demonstrated to be efficient electrode materials for supercapacitors. The best-synthesized material among three aerogels is NS-rGOA3 having a BET surface area of 412 m 2 g −1, providing an efficient ion transport path for electrolyte ions and more energy storage sites. The supercapacitive behaviour of aerogels was studied in 0.5 M Na2 SO4 as an electrolyte. NS-rGOA3 with an N/S ratio of 7.74 showed excellent gravimetric specific capacitance of 931 F g −1 at 1 A g −1 current density with a wide potential window of 1.2 V in an aqueous medium. The material shows a specific capacitance of 391.6 F g −1 even at a very high current density of 100 A g −1 . At a current density of 25 A g −1, it shows a specific capacitance of 541.6 F g −1 and 96% capacitance retention after 10 000 cycles. The as-fabricated symmetric supercapacitor device exhibits an energy density of 36.56 W h kg −1 and a power density of 333.2 W kg −1 .